Energetics (and mechanical determinants) of sprint and shuttle running - Zamparo, P.; Monte, A.; Pavei, G. (International Journal of Sports Medicine, 2024)
Unsteady locomotion (e. g., sprints and shuttle runs) requires additional metabolic (and mechanical) energy compared to running at constant speed. In addition, sprints or shuttle runs with relevant speed changes (e. g., with large accelerations and/or decelerations) are typically short in duration and, thus, anaerobic energy sources must be taken into account when computing energy expenditure. In sprint running there is an additional problem due to the objective difficulty in separating the acceleration phase from a (necessary and subsequent) deceleration phase.